Faw Grand Port and Its Impact on Sustainable Development in Iraq: Pelabuhan Besar Faw dan Dampaknya terhadap Pembangunan Berkelanjutan di Irak - Dakhel, Alaa Abbas; Sultan, Ibrahim Khalil (Indonesian Journal of Law and Economics Review, 2025)
<div class="min-h-8 text-message flex w-full flex-col items-end gap-2 whitespace-normal break-words text-start [.text-message+&]:mt-5" dir="auto" data-message-author-role="assistant" data-message-id="423bf7d0-0f98-47a9-9f44-6c0cee900e10" data-message-model-slug="gpt-4o"> Transport is a key driver of economic growth, encompassing land, maritime, and air transport. Maritime transport is particularly vital for global trade, offering an affordable means of moving goods. Both developed and developing nations invest in commercial shipping fleets, modernize ports with advanced technology, and enhance operational systems to stimulate foreign trade. Iraqi ports play a crucial role in national economic development, prompting the government to revitalize existing ports and construct new ones. One significant initiative is the Grand Faw Port, a strategic project within the dry canal corridor, connecting the Arabian Gulf through Basra’s ports to the Mediterranean via Syria and to Northern Europe through Turkey. This port aims to strengthen Iraq’s role in global trade, drive economic progress, and support sustainable development by improving logistics and transport efficiency. By establishing Grand Faw Port, Iraq seeks to enhance its commercial shipping capacity, positioning itself as a major regional trade hub. The project is expected to create employment opportunities, boost investments, and contribute to long-term economic stability. As maritime trade continues to expand, the Grand Faw Port will serve as a catalyst for Iraq’s integration into international markets, reinforcing its economic resilience and global trade participation. Highlights: Transport drives economic growth through maritime trade and infrastructure development. Iraq develops Grand Faw Port to enhance global trade connectivity. The port boosts economic progress and supports sustainable development. Keywords: Faw Port, sustainable development, economic growth, transportation, trade